SPE Annual Technical Conference and Exhibition 2018
DOI: 10.2118/191607-ms
|View full text |Cite
|
Sign up to set email alerts
|

Activating Shale to Form Well Barriers: Theory and Field Examples

Abstract: Shale is a general term used for argillaceous (clay-rich) rocks which are the most abundant sediment on the earth. It is believed that clay rich rocks comprise more than 50-75% of the geologic column. Shale has very varying petrophysical and mechanical properties. Shale is in the most cases acting as a trap or seal for hydrocarbon migration, but has also in more recent years been targeted as a reservoir target in some basins. In some wells it has been observed on cement bond logs that shales in uncemented inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Effective plugs may be installed by reaming the drillhole over a relatively short section, which is preferably located adjacent to a clay, shale or salt rock layer. The reamed drillhole section will be filled with a suitable backfill material, which will be compacted by the overburden and plastic deformation of the surrounding rock [50,51], effectively isolating the disposal section from the surface and at the same time sealing the excavation disturbed zone. Similar plugs may be installed throughout the disposal section to compartmentalize the disposal section, reducing the risk of axial radionuclide transport to transmissive zones that may intersect the drillhole.…”
Section: Backfilling and Sealingmentioning
confidence: 99%
“…Effective plugs may be installed by reaming the drillhole over a relatively short section, which is preferably located adjacent to a clay, shale or salt rock layer. The reamed drillhole section will be filled with a suitable backfill material, which will be compacted by the overburden and plastic deformation of the surrounding rock [50,51], effectively isolating the disposal section from the surface and at the same time sealing the excavation disturbed zone. Similar plugs may be installed throughout the disposal section to compartmentalize the disposal section, reducing the risk of axial radionuclide transport to transmissive zones that may intersect the drillhole.…”
Section: Backfilling and Sealingmentioning
confidence: 99%
“…Figure 1 represents schematically how the P&A is performed currently (Figures 1A,B) and the proposed "shale as a barrier" concept (Figure 1C). Creep, i.e., time dependent plastic deformation, has been identified as the main shale deformation mechanism [5]. It has been suggested that this phenomenon can potentially be useful in P&A [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Creep, i.e., time dependent plastic deformation, has been identified as the main shale deformation mechanism [5]. It has been suggested that this phenomenon can potentially be useful in P&A [4,5]. Indeed, it has been confirmed in downscaled laboratory experiments that some shales like e.g., Lark-Horda can efficiently seal off annulus [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective plugs may be installed by reaming the drillhole over a relatively short section that is preferably located adjacent to a clay, shale or salt rock layer. The reamed drillhole section will be filled with a suitable backfill material, which will be compacted by the overburden and plastic deformation of the surrounding rock[Kristiansen et al, 2018;Vrålstad et al 2019], effectively isolating the disposal section from the surface and at the same time sealing the excavation disturbed zone.…”
mentioning
confidence: 99%